EFEKTIVITAS PELAKSANAAN PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA - Sari, Cica Nopika; Heriyanto, Meyzi; Rusli, Zaili (Jurnal Ilmu Administrasi Negara, 2019)
Effectiveness Program Implementation of Community Empowerment-BasedCommunity Empowerment. This study aims to describe the effectiveness of the implementationof PMBRW in Meranti Village, Rumbai District, Pekanbaru City. This study uses a qualitativedescriptive research method approach. Primary data was obtained directly through interviews fromkey informants, namely the Village Head, the Facilitator Team leader, the RW Companion, theChairperson of the RT / RW Forum. Secondary data is obtained from research documents. Theresults showed that the implementation of the PMBRW program started from the preparationstage, planning stages and implementation stages and viewed from the criteria in terms ofachieving goals, integration and adaptation, that the community empowerment program in MerantiVillage was considered effective.